Screening for distress and needs: Findings from a multinational validation of the Adolescent and Young Adult Psycho‐Oncology Screening Tool with newly diagnosed patients. Issue 11 (30th June 2021) - Patterson, Pandora; D'Agostino, Norma M.; McDonald, Fiona E. J.; Church, Terry David; Costa, Daniel S. J.; Rae, Charlene S.; Siegel, Stuart E.; Hu, James; Bibby, Helen; Stark, Dan P.; ,
Abstract: Objective: Adolescents and young adults (AYAs) diagnosed with cancer commonly experience elevated psychological distress and need appropriate detection and management of the psychosocial impact of their illness and treatment. This paper describes the multinational validation of the Distress Thermometer (DT) for AYAs recently diagnosed with cancer and the relationship between distress and patient concerns on the AYA‐Needs Assessment (AYA‐NA). Methods: AYA patients ( N = 288; 15–29 years, M age = 21.5 years, SD ag e = 3.8) from Australia ( n = 111), Canada ( n = 67), the UK ( n = 85) and the USA ( n = 25) completed the DT, AYA‐NA, Hospital Anxiety Depression Scale (HADS) and demographic measures within 3 months of diagnosis. Using the HADS as a criterion, receiver operating characteristics analysis was used to determine the optimal cut‐off score and meet the acceptable level of 0.70 for sensitivity and specificity. Correlations between the DT and HADS scores, prevalence of distress and AYA‐NA scores were reported. Results: The DT correlated strongly with the HADS‐Total, providing construct validity evidence ( r = 0.65, p < 0.001). A score of 5 resulted in the best clinical screening cut‐off on the DT (sensitivity = 82%, specificity = 75%, Youden Index = 0.57). Forty‐two percent of AYAs scored at or above 5. 'Loss of meaning or purpose' was the AYA‐NA item most likely to differentiate distressed AYAs. Conclusions: The DT is a valid distress screening instrument for AYAs with cancer. The AYA‐POST (DT and AYA‐NA) provides clinicians with a critical tool to assess the psychosocial well‐being of this group, allowing for the provision of personalised support and care responsive to individuals' specific needs and concerns.